XRF ニヨル ショウワキチ タイキチュウ フユウリュウシジョウ ブッシツ ノ トクセイカ - 青山, 朋樹; アオヤマ, トモキ; 浅野, 比; アサノ, ヒトシ; 菊地, 正; キクチ, タダシ; 和田, 誠; ワダ, マコト; Aoyama, Tomoki; Asano, Hitoshi; Kikuchi, Tadashi; Wada, Makoto (2010)
P(論文) 本研究では,南極昭和基地に蛍光X線分析顕微鏡を持ち込んで大気中浮遊粒子状物質の分析を行い,各成分の季節変化を調査した.粒子状物質は海洋起源であるNa,Mg,S,Cl,K,Caを多く含むことが明らかとなった.また,ブリザードなどの強風時には土壌起源と考えられるSi,Feも検出されたことから,強風によって土壌成分が巻き上げられていることが示唆される.Sは夏季に増加し,冬季に減少する傾向を示した.S以外の海洋起源粒子は夏季に減少し,ブリザード時に増加する傾向を示した. The particle size distribution has been continuously measured by optical particle counter at Syowa Station. Physical and chemical properties of particulate matter have been analyzed in the laboratory after arriving in Japan. However, the properties of particles may be changed in this case. In the present work, the atmospheric particulate matter at Syowa Station, Antarctica was characterized by X-ray fluorescence spectroscopy (XRF) at Syowa Station. The advantages of this method have non destructive, rapid and simple analysis. The particle samples were collected on a Teflon filter; the obtained particles were measured by XRF (HORIBA, X-ray Analytical Microscope XGT-5000) on site soon for elemental analysis. The obtained results show that collected particles mainly contain sea salt (Na, Mg, Cl, K, Ca) and soil (Si, Fe) origin components. The particles from sea salt and soil origin increased under blizzard and strong wind condition. Sulfur increased in summer, and decreased in winter while particles from sea salt decreased in summer. departmental bulletin paper